Pembinaan Ibadah Shalat Pada Anak dalam Keluarga - Andi Aslindah; Reni Ardiana (Communio: Jurnal Pengabdian Kepada Masyarakat, 2023)
The most important and first role of the family is in instilling religious values, including fostering prayer worship which is one of the obligations for Muslims. In fostering prayer worship for children, including for early childhood, it is a job that requires time and high patience. Not only occasionally in instilling the habit of worshiping prayers and other religious and moral values in children, but it should be continuous and uninterrupted. However, fostering prayer worship from an early age in children is not an easy job. Because in reality there are not a few children who have reached the age of puberty but have not performed the prayers regularly and correctly. Therefore, parents need to understand the methods and patterns of coaching what needs to be done in instilling the habit of praying in children from an early age.